Bacteroides and NAFLD: pathophysiology and therapy - Zhang, Jun; Zhou, Jing; He, Zheyun; Li, Hongshan (Frontiers in Microbiology, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a prevalent chronic liver condition observed globally, with the potential to progress to non-alcoholic steatohepatitis (NASH), cirrhosis, and even hepatocellular carcinoma. Currently, the US Food and Drug Administration (FDA) has not approved any drugs for the treatment of NAFLD. NAFLD is characterized by histopathological abnormalities in the liver, such as lipid accumulation, steatosis, hepatic balloon degeneration, and inflammation. Dysbiosis of the gut microbiota and its metabolites significantly contribute to the initiation and advancement of NAFLD. Bacteroides, a potential probiotic, has shown strong potential in preventing the onset and progression of NAFLD. However, the precise mechanism by which Bacteroides treats NAFLD remains uncertain. In this review, we explore the current understanding of the role of Bacteroides and its metabolites in the treatment of NAFLD, focusing on their ability to reduce liver inflammation, mitigate hepatic steatosis, and enhance intestinal barrier function. Additionally, we summarize how Bacteroides alleviates pathological changes by restoring the metabolism, improving insulin resistance, regulating cytokines, and promoting tight-junctions. A deeper comprehension of the mechanisms through which Bacteroides is involved in the pathogenesis of NAFLD should aid the development of innovative drugs targeting NAFLD.